Identification and Characterization of a Tissue-Specific Coactivator, GT198, That Interacts with the DNA-Binding Domains of Nuclear Receptors - Ko, Lan (American Society for Microbiology, 2002)
Gene activation mediated by nuclear receptors is regulated in a tissue-specific manner and requires interactions between nuclear receptors and their cofactors. Here, we identified and characterized a tissue-specific coactivator, GT198, that interacts with the DNA-binding domains of nuclear receptors. GT198 was originally described as a genomic transcript that mapped to the human breast cancer susceptibility locus 17q12-q21 with unknown function. We show that GT198 exhibits a tissue-specific expression pattern in which its mRNA is elevated in testis, spleen, thymus, pituitary cells, and several cancer cell lines. GT198 is a 217-amino-acid nuclear protein that contains a leucine zipper required for its dimerization. In vitro binding and yeast two-hybrid assays indicated that GT198 interacted with nuclear receptors through their DNA-binding domains. GT198 potently stimulated transcription mediated by estrogen receptor α and β, thyroid hormone receptor β1, androgen receptor, glucocorticoid receptor, and progesterone receptor. However, the action of GT198 was distinguishable from that of the ligand-binding domain-interacting nuclear receptor coactivators, such as TRBP, CBP, and SRC-1, with respect to basal activation and hormone sensitivity. Furthermore, protein kinase A, protein kinase C, and mitogen-activated protein kinase can phosphorylate GT198 in vitro, and cotransfection of these kinases regulated the transcriptional activity of GT198. These data suggest that GT198 is a tissue-specific, kinase-regulated nuclear receptor coactivator that interacts with the DNA-binding domains of nuclear receptors.